Optimization of Polypropylene Composites for Automotive Applications: The Role of Carbon Fiber and Aluminum Oxide - Melyna, Ella; Muhammad Fadhillah Ansyari; Vina Kusuma Wardani (Jurnal Serambi Engineering, 2025)
The development of lightweight yet mechanically strong materials is crucial for automotive components. This study investigates the effects of carbon fibre (CF) and aluminium oxide (Al₂O₃) as fillers in polypropylene (PP) composites to improve their mechanical properties and thermal stability. Four variations of carbon fibre addition (0%, 10%, 20% and 30% by weight) were tested. The composites were prepared using a manual moulding machine (MFM) and evaluated for tensile strength, impact strength, crystallinity and thermal stability using a universal testing machine (UTM), impact tester, differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA). The results showed that the addition of carbon fibre reduced tensile strength but significantly improved impact strength, crystallinity and thermal stability. The optimum carbon fibre content was found to be 30% by weight for maximum impact strength and 20% for maximum crystallinity. This research provides insight into the application of carbon fibre and aluminium oxide reinforced polypropylene composites in the automotive industry.